Advanced template matching algorithm for instantaneous heartbeat detection using continuous wave radar systems - Will, Christoph; Kilin Shi; Weigel, Robert; Koelpin, Alexander (2017 First IEEE MTT-S International Microwave Bio Conference (IMBIOC), 2017)
Instantaneous heartbeat detection is a key parameter in modern vital sign monitoring. Continuous wave (CW) radar systems enable contactless measurements of the vibrations on the human skin effected by heartbeats. Since a high accuracy as well as robustness of the measurement sensor is appreciated, the belonging signal processing routine has to deal with challenging requirements. In this paper, an advanced template matching (ATM) algorithm is proposed to enhance the performance regarding instantaneous heartbeat detection using CW radar systems. Compared to common template matching algorithms, multiple heterogeneous templates are utilized in this approach, at which the appropriate template type is determined by prior feature detection. A 24 Ghz Six-Port microwave interferometer is used for vital sign measurements of a person-under-test. The functionality of the proposed algorithm is verified by a synchronous reference electrocardiogram (ECG) and its enhancement is shown by reducing the root-mean-square error (RMSE) of the interbeat intervals (IBI) compared to an ordinary template matching algorithm.